Syngas production from methane dry reforming over CeO2 promoted Ni/CaFe2O4 catalyst - Hossain, Mohammed Anwar (2019)
There is a growing interest in methane dry reforming as a technological route for producing synthesis gas (syngas) due to the benefits of utilizing methane (CH4) and carbon dioxide (CO2), the two principal components of greenhouse gases as feed stocks to Fischer-Tropsch synthesis of liquid hydrocarbons and oxygenates. Nevertheless, one of the major constraints of the methane dry reforming reaction is catalyst deactivation by sintering and carbon deposition. Approaches such as the synthesis of metal-based catalysts on suitable supports and the use of appropriate promoters have been reported to enhance catalyst resistance to deactivation and also improve their activities. This study is aimed at investigating the effect of using calcium ferrite (CaFe2O4) as support and cerium oxide (CeO2) as promoter on the activities and stabilities of Ni catalyst in methane dry reforming. Both the unpromoted and the CeO2-promoted Ni/CaFe2O4 catalysts were synthesized using wet impregnation method. The as-synthesized catalysts were subsequently characterized for their physicochemical properties by thermogravimetric analysis (TGA), X-ray diffraction (XRD), N2-physisorption analysis, Scanning electron microscope-Energy dispersive X-ray (SEM-EDX), Transmission electron microscopy (TEM), NH3 and CO2 temperature programmed desorption (TPD-NH3 and TPD-CO2) and H2-temperature programmed reduction (TPR). The catalytic activities and stabilities of the catalysts were investigated in methane dry reforming to syngas in a fixed bed stainless steel reaction at temperature range of 973-1073 K, under atmospheric pressure. In addition, the modelling and optimization study of the syngas production by methane dry reforming over the Ni/CaFe2O4 catalyst was conducted. The catalysts characterization shows that both the promoted and the unpromoted catalysts with pore diameter of 3.2 nm and 3.08 nm, respectively possessed mesopores (pore diameter > 2 nm) suitable for catalytic reaction such methane dry reforming. Moreover, the H2-TPR as well as the TPD-NH3 and TPD-CO2 show good reducibility of the nickel oxides and the presence of both acidic and basic sites. The CeO2 promoted Ni/CaFe2O4 catalyst displayed better catalytic activity compared to the unpromoted Ni/CaFe2O4 catalyst due to the preservation of the catalyst active site by the promotional effect of the CeO2. At feed (CH4: CO2) ratio of 1, and reaction temperature of 1073 K, the highest CH4 and CO2 conversions of 92.5%, and 91.2% respectively were obtained compared to 90.4% and 83.5% values obtained as CH4 and CO2 conversions from the methane dry reforming over the unpromoted catalyst. The deactivation of the unpromoted Ni/CaFe2O4 catalyst can be attributed to carbon deposition evidenced from the characterization of the used catalysts. The fitting of the rate data obtained from the methane dry reforming over the CeO2-promoted Ni/CaFe2O4 catalyst in LH model yielded an activation energy of 22.58 kJ/mol, which is comparable to those obtained from the literature. This implies that the kinetic model that fit the data is based on single site dissociative adsorption of both CH4 and CO2 with bimolecular surface reaction. The response surface methodology (RSM) studies showed that the process parameters (reaction temperature, feed ratio and GHSV) significantly influence the four responses (CH4 conversion, CO2 conversion, H2 yield and CO yield). Moreover, the interactions between these parameters were also found to significantly affect the responses. The optimization studies over the CeO2-promoted Ni/CaFe2O4 catalyst using RSM revealed that optimum conditions (Temperature = 1019 K, feed ratio= 0.98, GHSV= 28000 mL g-1 h-1) resulted in the maximum values of 93.76, 92.45, 77.54 and 79.17% for the CH4 conversion, CO2 conversion, CO yield, and H2 yield, respectively.